Serum biomarker CD163 predicts overall survival in patients with pancreatic ductal adenocarcinoma - Qinglin Fei, MD; Yu Pan, MD, PhD; Xingxing Yu, MD; Ronggui Lin, MD, PhD; Xianchao Lin, MD, PhD; Heguagn Huang, MD (Journal of Pancreatology, 2020)
Abstract. The serum soluble CD163 (sCD163) is elevated in patients with inflammatory disease and several types of cancer. However, the prognostic value of serum sCD163 in pancreatic ductal adenocarcinoma (PDAC) has not yet been investigated. In this study, serum level of sCD163 was measured by using the peripheral blood of 54 patients with PDAC, 20 patients with benign tumor of pancreas, and 30 healthy volunteers (healthy controls). The association between serum sCD163 level and overall survival was analyzed. Receiver operating characteristic (ROC) curves were generated, and areas under the curve (AUC) were compared to evaluate the diagnostic accuracy, including CA 19-9, CEA, CA 125, CA 153, and serum sCD163 level. Serum sCD163 level of patients with PDAC was significantly higher than patients with benign tumor (P = .002) and health controls (P < .001). Using ROC curves, we found that the AUC values of serum sCD163 were higher than those of CA 125 and CA 153, but lower than those of CA 19-9 and CEA. Serum sCD163 was negatively correlated with lymphocyte to monocyte ratio (LMR; r = −0.428, P = .001). In addition, the prognosis of PDAC patients with sCD163 ≥ median was worse than sCD163 < median by using univariate analysis (P = .027). Further, multivariate analysis showed that higher level of serum sCD163 was still associated with poorer overall survival (P = .020). In conclusion, the serum sCD163 has the potential as a new promising parameter to predict the prognosis in PDAC patients.